Mods and Rockers, Drunken Debutants, and Sozzled Students - Bill Thompson; Cecil Greek (SAGE Open, 2012)
Over the last decade, moral panic theory has affected a paradigm shift in the social construction of deviance and social problems in the United States, without any real debate about its viability. This article raises key questions about this perspective by offering the first ever critique of the seminal case study of British youth subcultures on which the paradigm is based. It argues that when analyzed in the context of contemporary criticism of vandalism, hooliganism, and delinquency, the Mods and Rockers case study never justified Cohen’s original criteria for a moral panic.